Eksplorasi Persepsi Kualitas Layanan Pasien Rawat Jalan Dengan Pendekatan Tri Hita Karana - Ayu Widyasari; Ni Nyoman Sunariani (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACTThe purpose of this study is to determine the perception as well as what factors should be improved to improve the quality of outpatient services with the concept approach Tri Hita Karana in Kasih Ibu Hospital Denpasar. The quality of service used in five dimensions is in accordance with the theory of Parasuraman et al., In Tjiptono (2016), in health care namely tangibles, reliability, responsiveness, assurance and empathy. Tri Hita Karana concept consists of three elements namely parhyangan, pawongan and attenuation. Informants in this study are outpatient, Head of Outpatient Installation, Polyclinic Manager, Head Division Frontliner and Head of Sub Division of Care Service RSU Kasih Ibu Denpasar. With this type of descriptive qualitative research. To ensure the credibility of the data is done techniques examination of data validity by triangulation technique. Result of research in service quality at service of Kasih Ibu Hospital Denpasar beside that approach of local wisdom of Tri Hita Karana executed well and according to existing SOP, perception to service quality of outpatient service good and got positive response from every informant. Factors that need to be improved to improve the quality of outpatient services are in the dimensions of responsiveness and dimensions of tangibles without any curative to other dimensions. Judging from the concept of Tri Hita Karana need improvement in element of pawongan and palemahan.